Improper Responsibility of Notary Candidates - Randy Esa Wibowo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2019)
This study uses normative juridical legal researchby examining laws and regulations. One of the requirements to be fulfilled by a Notary Candidate to be appointed as a Notary is to perform an apprenticeship for 24 (twenty four) months at the Notary's office, as referred to in Article 3 letter f UUJN. This research resulted in formulation of problem why Notary Candidate is required to conduct apprenticeship activities at Notary Office and Notary Candidate’s responsibility in improper apprenticeship activities at Notary's office. Notary candidates are required to conduct internship activities based on 2 (two) points in accordance with laws and regulations governing Notary Position and to improve the skills of Notary Candidates. Notary candidates who do not perform apprenticeship activities properly in Notary office cannot be sanctioned by the UUJN Because the UUJN only regulates the Notary Position. Instead, Notary recipient of an internship can be subject to criminal sanctions for counterfeiting a letter in accordance with article 55 paragraph (1) juncto Article 263 of the Criminal Code if it is later proven to issue an Internship Certificate as one of the requirements to be appointed as a Notary which is not in accordance with reality.